Corporate Borrowing and Credit Constraints: Structural Disequilibrium Estimates for the U.K. - Martin, Christopher (The Review of Economics and Statistics, 1990)
This paper develops a structural model of the market for corporate borrowing in the United Kingdom. The authors allow trade to be dispersed across a number of submarkets and suppose that disequilibrium operates at this disaggregated level. Solving for the level of aggregate trade, they can estimate nonlinear equations for the demand and supply of borrowing and for the associated interest rate. The authors use survey data to measure the strength of spillover from other markets. The estimates reveal that disequilibrium has had substantial effects. The authors also obtain interesting and plausible estimates for the parameters of the behavioral equations. Copyright 1990 by MIT Press.